Brain ventricular enlargement in human and murine acute intermittent porphyria. (11th September 2020) - Jericó, Daniel; Luis, Elkin O; Cussó, Lorena; Fernández-Seara, María A; Morales, Xabier; Córdoba, Karol M; Benito, Marina; Sampedro, Ana; Larriva, María; Ramírez, María J; de Salamanca, Rafael Enríquez; Ortiz-de-Solorzano, Carlos; et al.
Abstract: The morphological changes that occur in the central nervous system of patients with severe acute intermittent porphyria (AIP) have not yet been clearly established. The aim of this work was to analyze brain involvement in patients with severe AIP without epileptic seizures or clinical posterior reversible encephalopathy syndrome, as well as in a mouse model receiving or not liver-directed gene therapy aimed at correcting the metabolic disorder. We conducted neuroradiologic studies in 8 severely affected patients (6 women) and 16 gender- and age-matched controls. Seven patients showed significant enlargement of the cerebral ventricles and decreased brain perfusion was observed during the acute attack in two patients in whom perfusion imaging data were acquired. AIP mice exhibited reduced cerebral blood flow and developed chronic dilatation of the cerebral ventricles even in the presence of slightly increased porphyrin precursors. While repeated phenobarbital-induced attacks exacerbated ventricular dilation in AIP mice, correction of the metabolic defect using liver-directed gene therapy restored brain perfusion and afforded protection against ventricular enlargement. Histological studies revealed no signs of neuronal loss but a denser neurofilament pattern in the periventricular areas, suggesting compression probably caused by imbalance in cerebrospinal fluid dynamics. In conclusion, severely affected AIP patients exhibit cerebral ventricular enlargement. Liver-directed gene therapy protected against the morphological consequences of the disease seen in the brain of AIP mice. The observational study was registered at Clinicaltrial.gov as NCT02076763.